A class of globally stabilizing feedback controllers for the orbital rendezvous problem. (31st March 2017) - Leomanni, Mirko; Bianchini, Gianni; Garulli, Andrea; Giannitrapani, Antonio
Summary: The development of feedback control systems for autonomous orbital rendezvous is a key technological challenge for next‐generation space missions. This paper presents a new class of control laws for the orbital rendezvous problem. The controllers belonging to this class are guaranteed to globally asymptotically stabilize the relative dynamics of two satellites in circular or elliptic orbits. The proposed design procedure builds on control techniques for nonlinear systems in cascade form, by exploiting the geometric properties of the orbital element description of the satellite motion. A numerical simulation of a formation flying mission demonstrates the effectiveness of this approach for long‐range and low‐thrust rendezvous operations. Copyright © 2017 John Wiley & Sons, Ltd.